Diagnostic pathways leading to arrhythmogenic left ventricular cardiomyopathy in a single center cohort. (3rd October 2022) - Parisi, V; Graziosi, M; Ditaranto, R; Chiti, C; Caponetti, A G; Minnucci, M; Baldassarre, R; Di Nicola, F; Catalano, C; Saturi, G; Berardini, A; Pasquale, F; et al.
Abstract: Background: Despite major advances, the recognition of arrhythmogenic left ventricular cardiomyopathy (ALVC) remains challenging, since this clinical entity is often concealed in different clinical settings both in terms of clinical onset and imaging phenotype, resulting in significant delays in diagnosis with prognostic implications. Purpose: To describe a single Center cohort of ALVC patients, focusing on the spectrum of clinical presentation and diagnostic pathways. Methods: Patients were retrospectively evaluated between January 2012 and January 2022. Diagnosis was based on 1) ≥3 contiguous segments with subepicardial/midwall LGE in the LV at cardiac magnetic resonance (CMR) plus a likely pathogenic/pathogenic arrhythmogenic cardiomyopathy (ACM) associated genetic mutation and/or familial history of ACM and/or red flags for ALVC (i.e, negative T waves in V4–6/aVL, low voltages in limb leads) or 2) pathology examination of explanted hearts/autoptic cases suffering from sudden cardiac death (SCD). Patients with significant right ventricular involvement were excluded. Results: Sixty-six patients were evaluated for suspected ALVC: 8 phenocopies were excluded (6 acute myocarditis and 2 sarcoidosis) after a comprehensive clinical and multi-modality instrumental evaluation. The final study cohort was composed by 56 patients (55% males, median age 45 years), from 36 families. Diagnostic pathways leading to diagnosis were: SCD in 4 (7%), ventricular arrhythmias in 11 (20%), chest pain in 9 (16%), heart failure in 7 (12%), and familial screening in 25 (45%) (Figure 1). An echocardiogram was available for all but 2 patients with SCD: 25 (46%) had normal phenotype, 17 (32%) had a hypokinetic non dilated cardiomyopathy, and 12 (22%) had a dilated cardiomyopathy (DCM). Of the 49 tested patients, 31 (63%) had a pathogenic/likely pathogenic DNA variant: desmoplakin (DSP, N=21), filamin C (FLNC, N=4), SCN5A (N=3) were the most frequently involved genes; 8 patients had a double gene mutation. Twenty-four patients (43%) had previously received a diagnosis other than ALVC: 10 idiopathic DCM, 9 acute myocarditis, 4 post-myocarditis DCM, 2 acute myocardial injury/non-ST elevated myocardial infarction. In 13 patients ALVC was diagnosed with the introduction of CMR in the diagnostic work-up of a DCM, in 2 cases the diagnosis was done with the pathology examination after heart transplantation. The median diagnostic delay was of 8 years, with a maximum of 20 years. It is worth nothing that patients from the same family might have different diagnostic pathways and phenotypes of ALVC (Figure 2). Conclusions: ALVC is a challenging diagnosis, hidden in different clinical scenarios. Five main clinical pathways leading to ALVC diagnosis may be identified: ventricular arrhythmias, chest pain, heart failure, SCD at first presentation, and clinical/instrumental familial screening. Funding Acknowledgement: Type of funding sources: None.